Relationship Between Diet and Gangrene Degree in Diabetes Mellitus Patients - Tasya, Aisya Medina; Handayani, Astri (Bioscientist : Jurnal Ilmiah Biologi, 2024)
Diabetes Mellitus (DM) is a metabolic disease characterized by hyperglycemia caused by defects in insulin secretion, insulin action, or both. The number of people with DM has increased to approximately 463 million individuals aged 20-79 worldwide. Several complications can arise due to DM, one of which is gangrene wounds. Gangrene wounds are the most common microvascular complication in DM patients. Nutritional intake is a crucial component in the wound healing process. The aim of this study is to determine the relationship between diet and the degree of gangrene in DM patients. The method used is an observational analytical approach with a cross-sectional design. The sample size consists of 51 respondents obtained from medical records and questionnaires filled out by DM patients. Data analysis was conducted using the Chi-Square test. The results showed that 23 respondents had a moderate diet (45.1%), and the majority of respondents had wounds classified as degree 3 (21.6%). A significant relationship was found between diet and the degree of gangrene in DM patients (p<0.005). Thus, it can be concluded that a significant relationship exists between diet and the degree of gangrene in DM patients